Multicultural Education And The Internet Intersections and Integrations - Paul C.Gorski (McGraw Hill, 2005)
This book contained practical resource for exploring multicultural education on the internet. The text includes an overview of the internet and its current multicultural resources, a critical examination of the role of technology